Challenges and Opportunities of Traditional Agriculture in The Era of Food Security - Yohanes Kamakaula; Yunita Palinggi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
ABSTRACT As with previous qualitative studies using a descriptive approach, qualitative research using a descriptive approach functions to describe the main topics used in this study including traditional agriculture, resilience, challenges, and opportunities for traditional agriculture. The data used in this study are secondary data that researchers obtain from credible websites, scientific articles, books, and various other sources used in each study. Challenges and Opportunities for traditional agriculture are analyzed using the SWOT analysis tool with more comprehensive results below. The conclusion in this article show that traditional agriculture has more threats and weaknesses than strengths and advantages. Its strengths and opportunities can also be eroded slowly if technological advances in the era of modern agricultural food security are increasingly unstoppable. The strengths and opportunities in question include having machines that are more often used by the community and literacy around agriculture is not yet evenly distributed. While the weaknesses and threats are slow production, old-fashioned, Lagging behind technological advances, Low food security, Decreasing production, and Market dominated by modern agriculture.